Determining the effective hydrogen diffusion coefficient in 100Cr6. Issue 6 (25th February 2020) - Kürten, Dominik; Khader, Iyas; Kailer, Andreas
Abstract: In the present study, the diffusion constant for hydrogen in hardened 100Cr6 was measured in permeation tests. The tests were conducted on samples of different thicknesses. The diffusivity of hydrogen was also measured in prestrained samples to study the influence of plastic strain on the diffusion rate. A finite element‐based diffusion model was applied to confirm the experimental results by computing the concentrations of diffusible hydrogen and trapped hydrogen due to deformation‐induced defects. The results showed that the concentration of trapped hydrogen remained very low throughout the plastic strain regime under consideration. The average effective diffusion coefficient of hydrogen in 100Cr6 at 30°C was found to be D eff = 4.9 × 10 −12 m 2 /s. Abstract : The diffusion constant for hydrogen in hardened 100Cr6 was measured in permeation tests. The diffusivity of hydrogen was measured in prestrained samples to study the influence of plastic strain on the diffusion rate. A finite element‐based diffusion model was applied to confirm the experimental results by computing the concentrations of diffusible hydrogen and trapped hydrogen due to deformation‐induced defects.